Optical genome mapping reveals complex cytogenetic abnormalities in multiple myeloma - Jorge A. Palacios; Mónica Bernal; Jose R. Vílchez; Pilar Garrido; Pilar Jiménez; Juan F. Gutiérrez-Bautista; María C. Barrera-Aguilera; Lucía Ballesta; Teresa Rodríguez; María J. Olivares-Durán; Francisco Ruiz-Cabello (Haematologica)
Not available.